Adomian Modification Methods via Orthogonal Polynomials: A Comparative Study (European Journal of Pure and Applied Mathematics, 2024)
The present manuscript proposes different modification procedures for the standard Adomian Decomposition Method (ADM). These procedures are based on the application of orthogonal polynomials that play vital parts in approximation theories. Moreover, the study also scrutinizes four test nonlinear inhomogeneous initial-value problems, and distinctively examines their respective absolute error differences. Remarkably, different computational benefits of the proposed modification are noted with regard high-level of accuracy and fewer computational steps.
Keywords: ADM; modification methods; orthogonal polynomials; ODEs; IVPs.